Laksūt matthayomsưksā t̨ōn ton, Phutthasakkarāt 2521 : chabap prapprung, Ph̨ō. S̨ō. 2533 (Krom Wichākān, Krasūang Sưksāthikān, 1992)
Curricula for secondary education in Thailand, under the Educational Plan, 1978; a 1990 revision.